Public managers' role in creating workplace social capital (WSC) and its effect on employees' well-being and health: a protocol of a longitudinal cohort study (PUMA-WSC). Issue 10 (27th October 2020) - Pihl-Thingvad, Signe; Hansen, Sune W; Winter, Vera; Hansen, Michelle S; Willems, Jurgen
Abstract : Introduction: Workplace social capital (WSC) has been shown to affect employees' well-being and health, yet it is not clear how public managers can create WSC and which forms of WSC are most important. This study is the first prospective cohort study to examine the relationship between management behaviour, WSC, well-being and sickness absence. It uses a validated and detailed scale on WSC, which can distinguish between bonding, bridging, linking and organisational WSC over time. The study thereby provides rich data giving a much-needed detailed image of how WSC impacts on public employees' well-being and health. Additionally, the study pays special attention to the fact that these relationships can be different for different types of employees and therefore tests a set of relevant employee and context-related variables. Methods and analysis: Project preparations in terms of agreements and data preparation of existing data started in 2019. This prospective cohort study considers and collects organisational data from 2016 to 2025. Annual employee surveys of more than 8000 employees (in a large Danish municipality) will be combined with register data in all years. This generates a unique cohort of public employees in different professions that are traceable over several years. The annual surveys include information on the management behaviour, WSC and employee outcomes. Fine-grained information on sickness absences will be matched for all employees and years under study. Moreover, confounders and the nested nature of the data will be considered. Ethics and dissemination: Approval has been obtained from The Regional Committee on Health Research Ethics from Southern Denmark and from the University of Southern Denmark. The results will be presented at conferences and published in international peer-reviewed journals and in a practice-oriented monography targeted at public managers. The result will furthermore be disseminated to the involved employees through seminars and workshops in the participating organisations.